The Effectiveness of Legal Protection for Victims of Sexual Violence by the Child Protection Organization (LPA) Majalengka - Farichi, Mahfud (MIH FH UNSOED, 2024)
Article 18 of the Child Protection Law states that every child who is a victim or perpetrator of a criminal offense is entitled to legal protection. To realize the legal protection of children, the Child Protection Agency (LPA) is present to assist in providing legal protection to child victims of sexual violence, one example of the services provided is legal assistance. This article will reveal the effectiveness of legal protection and the inhibiting factors experienced by LPA. This article is a socio-legal research with primary data obtained from interviews at LPA Majalengka, an LPA located in West Java province. Majalengka is a district with a low level of reporting of sexual violence against children, which does not mean that statistically it is low but tends to be because people are confused and lack trust in the law enforcement process in cases like this. The results showed that the provision of legal assistance by the Child Protection Agency in collaboration with the Legal Counsel for children of sexual violence cannot be said to be effective, because there are still several obstacles in its implementation, starting from law enforcement officials, parents of perpetrators/victims as well as facilities and infrastructure and obstacles from the children themselves. Efforts made to overcome these obstacles require cooperation between related agencies to handle cases of victims of sexual violence against children, which can be achieved by holding regular meetings between agencies, namely, the LPA, police, prosecutors, courts, correctional centers, legal aid agencies, and non-governmental organizations that focus on children.